The role of creativity and innovation in commercializing the dairy sector: A case study of sham diaries of Morogoro - Mhando, Samiji Enea (Mzumbe University, 2024)
A dissertation submitted for in partial fulfillment of the requirements for the Masters degree in Entrepreneurship ( Msc. Entrepreneurship) of Mzumbe University.